Search for CP violation and a measurement of the relative branching fraction in D+ -> K-K+ pi(+) decays - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges-Pous, E; Palano, A; Pompili, A; et al. (2005)
We report on a search for the CP asymmetry in the singly Cabibbo-suppressed decays D+→K-K+π+ and in the resonant decays D+→π+ and D+→K̄*0K+ based on a data sample of 79.9fb-1 recorded by the BABAR detector. We use the Cabibbo-favored Ds+→K-K+π+ branching fraction as normalization in the measurements to reduce systematic uncertainties. The CP asymmetries obtained are ACP(K-K+π±)=(1.4±1.0(stat)±0. 8(syst))×10-2, ACP(π±)=(0.2±1.5(stat)±0.6(syst)) ×10-2, and ACP(K̄*0K±)=(0.9±1.7(stat)±0. 7(syst))×10-2. The relative branching fraction Γ(D+→K-K+π+)/ Γ(D+→K-π+π+) is also measured and is found to be (10.7±0.1(stat)±0.2(syst))×10-2. © 2005 The American Physical Society.